New Trends in Bioremediation Technologies Toward Environment-Friendly Society: A Mini-Review - Dutta, Kunal; Shityakov, Sergey; Khalifa, Ibrahim (Frontiers in Bioengineering and Biotechnology, 2021)
Today environmental balance has been compromised by the unreasonable and sometimes dangerous actions of humans in an attempt to dominate on earth. As a result, oceans are contaminated by the different types of plastic trash, crude oil coming from mismanagement of transporting ships spilling it in the water, air pollution due to increasing production of greenhouse gases, such as CO2, methane, etc. into the atmosphere. The lands, agricultural fields, and groundwater are also contaminated by the notorious chemicals viz. polycyclic aromatic hydrocarbons, pyrethroids pesticides, bisphenol-A, dioxanes, etc. Therefore, bioremediation might be a convenient alternative to fix the damaged environment. However, at present, the majority of bioremediation reports are limited to the natural capabilities of the microbial enzymes. Synthetic biology with uncompromised supervision of ethical standards could help to outsmart nature’s engineering, such as the CETCH cycle for improved CO2 fixation. Additionally, a blend of SynBio with machine learning algorithms could expand the possibilities of bioengineering. This review summarized current state-of-the-art knowledge of the data-assisted enzyme redesigning to actively promote new research on important enzymes to ameliorate the environment.